MICROHARDNESS DIFFERENCES BETWEEN SILK FIBER AS A NATURAL FILLER COMPOSITE RESIN WITH NANOFILLER COMPOSITE RESIN - Puspita, Sartika; Aziz, Romadhon Yuan; Nugroho, Dwi Aji (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Dental composite composed of natural filler is a trend nowadays. Silk fiber, Bombyx mori L., is one of the natural fibers that have good microhardness (66 VHN) and has a potency to become a renewable natural filler. This research aimed to determine microhardness differences of silk fiber composite B. mori L., and nanofiller composite resin as a gold standard.Method: A quasi-experimental laboratory using composite resin with silk fiber B. mori L., as a natural filler; nanofiller composite Z350 XT flowable (3M ESPE, USA) as a positive control and no-filler composite as a negative control. Four cylindrical specimens per group were made (d=3mm, h=6mm). Microhardness tests were done with Vickers hardness tester (Shimadzu, Japan). Indentation of 100 grams for 20 seconds.Result: There were significant differences in the natural filler, nanofiller group (positive) control and no-filler composite (negative control). Based on the Kruskal Wallis test result, there was a significant difference in microhardness (p=0.024). The highest microhardness was nanofiller (115,2 VHN), silk fiber filler (109,4 VHN), and no-filler composite (32,2 VHN).Conclusion: Silk fiber Bombyx mori L., has shown the good potential of being a renewable natural filler (109,4 VHN) however lower than nanofiller composites.